Cryo-Focused Ion Beam Lamella Preparation Protocol for in Situ Structural Biology - Moravcová, Jana; Dopitová, Radka; Pinkas, Matyáš; Nováček, Jiří (Methods in molecular biology, 2021)
The advances in electron cryo-microscopy have enabled high-resolution structural studies of vitrified macromolecular complexes in situ by cryo-electron tomography (cryo-ET). Since utilization of cryo-ET is generally limited to the specimens with thickness < 500 nm, a complex sample preparation protocol to study larger samples such as single eukaryotic cells by cryo-ET was developed and optimized over the last decade. The workflow is based on the preparation of a thin cellular lamella by cryo-focused ion beam milling (cryo-FIBM) from the vitrified cells. The sample preparation protocol is a multi-step process which includes utilization of several high-end instruments and comprises sample manipulation prone to sample deterioration. Here, we present a workflow for preparation of three different model specimens that was optimized to provide high-quality lamellae for cryo-ET or electron diffraction tomography with high reproducibility. Preparation of lamellae from large adherent mammalian cells, small suspension eukaryotic cell line, and protein crystals of intermediate size is described which represents examples of the most frequently studied samples used for cryo-FIBM in life sciences.
Keywords: Animals; Electron Microscope Tomography; Specimen Handling; Cells; Cryoelectron Microscopy; Saccharomyces cerevisiae; Reproducibility of Results; tomografie elektronová; Proteins; molekulární biologie; Workflow; Macromolecular Substances; reprodukovatelnost výsledků; proteiny; Molecular Biology; ionty; makromolekulární látky; Ions; elektronová kryomikroskopie; zvířata; odběr biologického vzorku; buňky; průběh práce